Targeting neurotrophin signaling in cancer: The renaissance. (September 2018) - Griffin, Nathan; Faulkner, Sam; Jobling, Phillip; Hondermarck, Hubert
Graphical abstract: Abstract: Nerve outgrowth in the tumor microenvironment (tumor neurogenesis) has recently been shown to be essential for cancer progression and the concept of nerve dependence is emerging in oncology. Neurotrophins such as nerve growth factor (NGF) have long been identified as drivers of neurogenesis during development and regeneration, but intriguingly they were also known to be expressed in human tumors where they can stimulate cancer cell growth. Recent findings have unraveled that NGF released by cancer cells is also a driver of tumor neurogenesis, via the stimulation of NGF receptors on nerve endings. In return, nerves infiltrated in the tumor microenvironment secrete neurotransmitters, which can stimulate both the growth of tumor cells and angiogenesis. This neurotrophic role of NGF in cancer is likely to be relevant to a large variety of human malignancies, as well as other neurotrophins, and may have ramifications in cancer pain. Therefore, pharmacological interventions against neurotrophin signaling have the potential not only to target cancer cells directly, but also to inhibit neurogenesis and its stimulatory impact on cancer progression and pain.